Qingfei Litan Decoction Against Acute Lung Injury/Acute Respiratory Distress Syndrome: The Potential Roles of Anti-Inflammatory and Anti-Oxidative Effects - Diao, Yirui; Ding, Qi; Xu, Gonghao; Li, Yadong; Li, Zhenqiu; Zhu, Hanping; Zhu, Wenxiang; Wang, Peng; Shi, Yuanyuan (Frontiers in Pharmacology, 2022)
Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is an acute respiratory failure syndrome characterized by progressive arterial hypoxemia and dyspnea. Qingfei Litan (QFLT) decoction, as a classic prescription for the treatment of acute respiratory infections, is effective for the treatment of ALI/ARDS. In this study, the compounds, hub targets, and major pathways of QFLT in ALI/ARDS treatment were analyzed using Ultra high performance liquid chromatography coupled with mass spectrometry (UHPLC-MS) and systemic pharmacology strategies. UHPLC-MS identified 47 main components of QFLT. To explore its anti-inflammatory and anti-oxidative mechanisms, gene ontology (Go) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment and network pharmacological analysis were conducted based on the main 47 components. KEGG enrichment analysis showed that TNF signaling pathway and Toll-like receptor signaling pathway may be the key pathways of ALI/ARDS. We explored the anti-inflammatory and anti-oxidative efficacy of QFLT in treatment of ALI/ARDS in vivo and in vitro. QFLT suppressed the levels of proinflammatory cytokines and alleviated oxidative stress in LPS-challenged mice. In vitro, QFLT decreased the levels of TNF-α, IL-6, IL-1β secreted by LPS-activated macrophages, increased GSH level and decreased the LPS-activated reactive oxygen species (ROS) in lung epithelial A549 cells. This study suggested that QFLT may have anti-inflammatory and anti-oxidative effects on ALI/ARDS, combining in vivo and in vitro experiments with systemic pharmacology, providing a potential therapeutic strategy option.